2013
DOI: 10.1177/1541931213571438
|View full text |Cite
|
Sign up to set email alerts
|

Role of Expectancy, Motion and Overhead Lighting on Nighttime Visibility

Abstract: More than half of the pedestrian fatalities occur at night. It is important to understand the factors that lead to pedestrian detection for designing and implementing effective countermeasures in order to reduce pedestrian fatalities. Research has shown that expectancy, motion and overhead lighting affect pedestrian visibility. This goal of this study is to understand the combined effect of these three factors on nighttime visibility. Twenty four participants were recruited to drive on a test track under diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Regardless of the research setting, the issue of expectancy can be problematic for any study of drivers' abilities to recognise the presence of pedestrians. Drivers who expect to encounter a pedestrian in a given location are likely to respond from a longer distance than drivers who are surprised by the pedestrian's presence . Drivers who expect to encounter a pedestrian may have different visual scanning patterns prior to encountering a pedestrian and are likely to respond more quickly once a pedestrian is perceived.…”
Section: Experimental Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the research setting, the issue of expectancy can be problematic for any study of drivers' abilities to recognise the presence of pedestrians. Drivers who expect to encounter a pedestrian in a given location are likely to respond from a longer distance than drivers who are surprised by the pedestrian's presence . Drivers who expect to encounter a pedestrian may have different visual scanning patterns prior to encountering a pedestrian and are likely to respond more quickly once a pedestrian is perceived.…”
Section: Experimental Approachesmentioning
confidence: 99%
“…Drivers who expect to encounter a pedestrian in a given location are likely to respond from a longer distance than drivers who are surprised by the pedestrian's presence. 77,88,89 Drivers who expect to encounter a pedestrian may have different visual scanning patterns prior to encountering a pedestrian and are likely to respond more quickly once a pedestrian is perceived. Indeed, most authors differentiate between 'conspicuity' and 'visibility', in that a pedestrian is said to be conspicuous when he or she is recognised as a pedestrian, even by a driver who had no advanced warning or special expectation of encountering a pedestrian in that particular location.…”
Section: Experimental Approachesmentioning
confidence: 99%
“…Previous research on pedestrian conspicuity demonstrated an increase in detection distance with expectancy. 35 This may explain why conspicuity aids appear to be more effective in simulated settings where test observers were primed to expect the target. In real driving conditions, however, drivers develop a visual search strategy which focuses on frequent, major dangers but filters out infrequent objects.…”
Section: Discussionmentioning
confidence: 99%
“…Targets. Targets were used to evaluate roadway visibility (by measuring detection distance in the visual performance experiment); these were grey in color and 0.18 3 0.18 m in size, similar to ones used in earlier work (18)(19)(20)(21)(22)(23)(24)(25). Targets were located 0.3 m outside the right shoulder of the road.…”
Section: Experimental Designmentioning
confidence: 99%